2020
DOI: 10.3390/ncrna6010008
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Hypoxia Inducible AtR8 Long Non-Coding RNA also Contributes to Plant Defense and Root Elongation Coordinating with WRKY Genes under Low Levels of Salicylic Acid

Abstract: AtR8 lncRNA was previously identified in the flowering plant Arabidopsis thaliana as an abundant Pol III-transcribed long non-coding RNA (lncRNA) of approximately 260 nt. AtR8 lncRNA accumulation is responsive to hypoxic stress and salicylic acid (SA) treatment in roots, but its function has not yet been identified. In this study, microarray analysis of an atr8 mutant and wild-type Arabidopsis indicated a strong association of AtR8 lncRNA with the defense response. AtR8 accumulation exhibited an inverse correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Studies have shown that plant root development can be regulated by ERF [ 38 ], WRKY [ 39 , 40 ], bHLH [ 41 43 ], MYB, and MYB-like [ 44 47 ], NAC [ 48 , 49 ], AP2 [ 50 , 51 ], and MADS-box [ 52 , 53 ] transcription factor (TF) genes. After exposure of Z .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that plant root development can be regulated by ERF [ 38 ], WRKY [ 39 , 40 ], bHLH [ 41 43 ], MYB, and MYB-like [ 44 47 ], NAC [ 48 , 49 ], AP2 [ 50 , 51 ], and MADS-box [ 52 , 53 ] transcription factor (TF) genes. After exposure of Z .…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, WRKY TFs often act as activators or repressors to modulate important plant processes [ 61 ]. For example, Li et al [ 39 ] showed that WRKY genes were involved in the root elongation in Arabidopsis , while Wang et al [ 40 ] reported a WRKY TF gene that could affect adventitious root formation in Catalpa Scop . MYB and MYB-like TF families are also important, as they are involved in controlling trichome development and root hair formation [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have proved that plant root development could be regulated by ERF [40], WRKY [41,42], bHLH [43][44][45], MYB and MYB-like [46][47][48][49], NAC [50,51], AP2 [52,53] as well as MADS-box [54,55] TF genes. After exposure to graphene treatment of Z. mays roots, there were three up and one down-regulated ethylene-responsive (ERF) transcription factor genes ( Fig.…”
Section: Transcription Factors Enriched In Maize Plants Exposed To Grmentioning
confidence: 99%
“…WRKY transcription factors are one of the largest families of transcriptional regulators in plants and WRKY proteins often act as activators or repressors to modulate important plant processes [63]. Li et al, [41] showed that WRKY genes were involved in the root elongation in Arabidopsis Hypoxia. Wang et al, [42] reported a WRKY transcription factor gene that could affect adventitious root formation in Catalpa Scop.…”
Section: Graphene-related Transcription Factor Genes Inz Maysmentioning
confidence: 99%
“…Genome-wide analyses of TF encoding genes revealed that they correspond to 20 % of plant genome (Iida et al 2005;Xiong et al 2005). These factors are important regulators of transcription of plant defense genes (Asai et al 2002;Singh et al 2002;Qiu et al 2007; Guo et al 2019;Li, Nayar, et al 2020). The WRKY TF group is the most studied TF family involved in plant stress responses.…”
Section: Introductionmentioning
confidence: 99%